Insights into Treponema pallidum genomics from modern and ancient genomes using a novel mapping strategy - Marta Pla-Díaz; Gülfirde Akgül; Martyna Molak; Louis du Plessis; Hanna Panagiotopoulou; Karolina Doan; Wiesław Bogdanowicz; Paweł Dąbrowski; Maciej Oziembłowski; Barbara Kwiatkowska; Jacek Szczurowski; Joanna Grzelak; et al. (BMC Biology)
Abstract Background Treponemal diseases are a significant global health risk, presenting challenges to public health and severe consequences to individuals if left untreated. Despite numerous genomic studies on Treponema pallidum and the known possible biases introduced by the choice of the reference genome used for mapping, few investigations have addressed how these biases affect phylogenetic and evolutionary analysis of these bacteria. In this study, we ascertain the importance of selecting an appropriate genomic reference on phylogenetic and evolutionary analyses of T. pallidum. Results We designed a multiple-reference-based (MRB) mapping strategy using four different reference genomes and compared it to traditional single-reference mapping. To conduct this comparison, we created a genomic dataset comprising 77 modern and ancient genomes from the three subspecies of T. pallidum, including a newly sequenced seventeenth century genome (35X mean coverage) of a syphilis-causing strain (designated as W86). Our findings show that recombination detection was consistent across different references, but the choice of reference significantly affected ancient genome reconstruction and phylogenetic inferences. The high-coverage W86 genome introduced in this study also provided a new calibration point for Bayesian molecular clock dating, improving the reconstruction of the evolutionary history of treponemal diseases. Additionally, we identified novel recombination events, positive selection targets, and refined dating estimates for key events in the species’ history. Conclusions This study highlights the importance of considering methodological implications and reference genome bias in high-throughput sequencing-based whole-genome analysis of T. pallidum, especially of ancient or low-coverage samples, contributing to a deeper understanding of the treponemal pathogen and its subspecies.